Student's Ability to Solve The Problem of The Comparison with Model Problem Based Learning in The Classroom Instruction VII Mts Noorhidayah Darussalam - paris, amin (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2017)
This study aims to determine the ability of solving mathematical problems by using model Problem Based Instruction and the effect of problem based learning model Instruction on students' problem-solving abilities. The research method used experimental method to the type of field research and quantitative approaches. The sample in this study were students of class VII-B MTs Noorhidayah Darussalam in comparison with the material research design One-group pretest-posttest design. Design Research, the study was conducted only in one class as a class experiment. The data analyzed were taken from the value pretest and posttest study siswa.Hasil get the result that the problem solving process of students in the material ratio is in conformity with the learning pace of Problem Based Instruction, and there are significant learning model of problem-based instruction to the student's ability in problems solving on material ratio. Key Words : problem solving in mathematics, problem based instruction, comparasion